2002
DOI: 10.3318/bioe.2002.102.3.129
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Ecosystem Function: Do Species Matter?

Abstract: Biological communities perform a variety of functions within ecosystems, including regulation of climatic processes, breakdown of waste, recycling of nutrients, maintenance of soil fertility and provision of natural resources. Although exact numbers and timescales are difficult to determine, it is clear that biodiversity (species and habitat richness, genetic diversity and community complexity) is declining. Studies of biodiversity are thus assuming greater significance as ecologists try desperately to documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 62 publications
(60 reference statements)
2
22
0
5
Order By: Relevance
“…Most studies have demonstrated that a reduction in biodiversity has a negative effect on ecosystem function (reviews in Loreau et al 2001;Giller and O'Donovan 2002;Hooper et al 2005). The majority of this work has been done on terrestrial plant communities, and results of 95% of the manipulation studies reviewed by Schwartz et al (2000) supported the redundant species hypothesis.…”
Section: Biodiversity Ecosystem Function and Ecosystem Servicesmentioning
confidence: 57%
See 1 more Smart Citation
“…Most studies have demonstrated that a reduction in biodiversity has a negative effect on ecosystem function (reviews in Loreau et al 2001;Giller and O'Donovan 2002;Hooper et al 2005). The majority of this work has been done on terrestrial plant communities, and results of 95% of the manipulation studies reviewed by Schwartz et al (2000) supported the redundant species hypothesis.…”
Section: Biodiversity Ecosystem Function and Ecosystem Servicesmentioning
confidence: 57%
“…There is, of course, the null hypothesis that no relationship exists between biodiversity and ecosystem function ( Fig. 1) but support for this is weak (Giller and O'Donovan 2002). The next simplest model (but also considered unlikely, Tilman 1997) is a linear relationship where each additional species contributes the same amount of ecosystem function (Fig.…”
Section: Biodiversity Ecosystem Function and Ecosystem Servicesmentioning
confidence: 99%
“…Spesis yang memberikan respon sama dikelompokkan dalam satu tipe fungsional yang sama dan spesis yang berbeda respon akan dikelompokan dalam tipe fungsional yang berbeda. Dalam hutan sekunder terdapat tujuh tipe kelompok fungsional (Tabel 4) yakni oppurtunist (1 spesis), generalized myrmicinae (1 spesis), specialis predator (4 spesis), tropical climate specialis (6 spesis), dominant Semut opportunist umumnya hidup pada areal yang terganggu sebagai akibat kehadiran manusia atau pada daerah dengan tingkat diversitas yang rendah (Giller, 2002). Habitat yang terganggu dapat mempengaruhi produktivitas semut dan tingkat keragamannya.…”
Section: Kelompok Fungsional Semutunclassified
“…Les caractéristiques écologiques de la diversité floristique attestent une stabilité fonctionnelle du système, au sein duquel la complexité d'interactions dynamiques est telle qu'une variation ou perturbation du milieu n'a qu'un faible impact (Bond et Chase, 2002 ;Giller et O'Donovan, 2002 ;Wallington et al, 2005 ;Caldeira et al, 2005 ;Mikkelson, 2009). Ce stade de développement intègre une étroite corrélation entre richesse spécifique et performance ou stabilité fonctionnelle de l'écosystème, traduisant généralement son état de développement.…”
Section: Introductionunclassified